Przyrzeczona - Dobrucki, Lesław (Poland : Krakow Film Foundation, 2010)
There are about 2.5 million Turkish minority members in Germany. Every year at least a dozen Turkish women are beaten to death by their husbands or other relatives. In Turkey, more than 300 so-called honor killings are committed annually while 40% of wives are victims of domestic violence. Little Bride reveals the story of a Turkish girl who was sent to Germany and forced to marry when she was 13 years old. Soon after her arrival her husband started abusing and beating her regularly. After several years of maltreatment she finally managed to escape and is now in hiding from both the tyrannical man and her family whom, according to traditional Turkish "family values," she dishonored by running away. Unable to rely on her Turkish kin, afraid to appeal to the German authorities, will she be able to pick up the shreds of her life?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films